2022
DOI: 10.3390/ijerph192113848
|View full text |Cite
|
Sign up to set email alerts
|

Life and Leisure Activities following Stroke or Transient Ischaemic Attack (TIA): An Observational, Multi-Centre, 6-Month Follow-Up Study

Abstract: Objective: To examine changes in leisure participation following stroke/transient ischaemic attack (TIA) and explore its relationship to modifiable and non-modifiable participant characteristics. Design: An observational study design with self-report questionnaires collected at two time points (baseline and 6-months). Setting: The study was conducted across 21 hospital sites in England, Wales, and Northern Ireland. Participants: Participants were aged 18+ and had experienced a first or recurrent stroke or TIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In the prior study, [ 16 ] it was identified that those participants who were older, female and living in an area of high socioeconomic deprivation were more likely to experience a reduction in leisure engagement. This sequential analysis identified that the main barriers for these groups were ‘ physical difficulties ’ and ‘lower energy levels ’ (as for all participants) and either loss of independence (older participants) or psychological difficulties (females or living in high socioeconomic deprivation).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the prior study, [ 16 ] it was identified that those participants who were older, female and living in an area of high socioeconomic deprivation were more likely to experience a reduction in leisure engagement. This sequential analysis identified that the main barriers for these groups were ‘ physical difficulties ’ and ‘lower energy levels ’ (as for all participants) and either loss of independence (older participants) or psychological difficulties (females or living in high socioeconomic deprivation).…”
Section: Resultsmentioning
confidence: 99%
“…This method enabled a more thorough understanding of specific issues and identified barriers and facilitators to engagement that were common to all participant groups. Building on the previous study’s findings of a 22% loss in activity post-stroke [ 16 ], this study helped to understand why this might happen and what might help to overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations